Implementatiton of Evaluation Registration Outpatient Computerized Hospital Using a Web-based Technology Accepted Model System - Yunita Wisda Tumarta Arif; Nabilatul Fanny; Dwi Puji Lestari (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
The Information of health system is combination of devices and procedures used for manage information cycle from data collection to providing feedback infomation, for support the implementation of appropriate actions in planning, implementation and monitoring of health system performance. Outpatient registration is the main service received at an outpatient registration. Technologi Accepted Model System created using the PHP programming language and mysql database. The WEB-based Technology Acceptance Model (TAM) is in the form of all evaluation models that can determine the readiness of officers to accept a system. Application of the Web-based Technology Accepted Model System in Evaluating officer acceptance of the computerized Outpatient Registration information system at a hospital in Boyolali, Central Java, Indonesia. The Technology Accepted Model in this study used 5 variables where the results of the implementation of the Technology Accepted Model System showed that the analysis of customer satisfaction with outpatient application systems on the Perceived ease of use dimension obtained satisfied results of (64.8%), on the Perceived usefulness dimension the results obtained satisfied by (63.3%), on the Attitude toward using dimension obtained satisfactory results of (64%), on the Behavioral intention to use dimension obtained appropriate results of (69%), on the Perceived service availability dimension obtained very satisfied results as large as (69 ,3%). Conclusions from the dimensions of Perceived ease of use, Perceived usefulness, Attitude toward using. Behavioral intention to use, and Perceived service availability indicate that officers are satisfied with the Outpatient Registration Application System at Hospitals